2010
DOI: 10.1097/psy.0b013e3181dbc0e9
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Cardiac Effects of Momentary Assessed Stressful Events and Worry Episodes

Abstract: Worry has effects on cardiac activity, and these effects were still visible after 2 hours. The latter finding suggests that a considerable part of prolonged activation may be induced by unconscious stress-related cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 31 publications
(30 reference statements)
5
95
0
Order By: Relevance
“…These suggestions are supported by both short term and long term studies on the cardiac response to stress and worry Brosschot and Thayer, 2003;Glynn, 2002;Pieper et al, 2007Pieper et al, , 2010Verkuil et al, 2009). For example, in a study of normal populations assessed by ambulatory monitoring, HRV decreased during periods when participants reported that they had been worrying .…”
Section: Introductionmentioning
confidence: 85%
“…These suggestions are supported by both short term and long term studies on the cardiac response to stress and worry Brosschot and Thayer, 2003;Glynn, 2002;Pieper et al, 2007Pieper et al, , 2010Verkuil et al, 2009). For example, in a study of normal populations assessed by ambulatory monitoring, HRV decreased during periods when participants reported that they had been worrying .…”
Section: Introductionmentioning
confidence: 85%
“…Perseverative cognition, including worry or rumination, may lead to difficulties initiating sleep (i.e., longer sleep latency), maintaining an adequate amount of sleep (i.e., sleep duration), and obtaining enough restorative sleep (i.e., sleep quality) to feel refreshed and energized upon awakening (i.e., daytime sleepiness; cf. Brosschot, Gerin, & Thayer, 2006;Pieper, Brosschot, van der Leeden, & Thayer, 2010;Zoccola, Dickerson, & Lam, 2009). Similarly, perseverative cognition has also been found to contribute to sleep disorders, particularly in insomnia (Morin, Vallières, & Ivers, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although studied to a lesser extent, the anticipatory effect of a stressful event on the cardiac autonomic control of HR (Hynynen et al 2009;Mateo et al 2011;Pieper et al 2007Pieper et al , 2010 could be also of considerable relevance for soccer referees. For instance, Hynynen et al (2009) reported no significant HRV differences between a control and a parachute jump day but an elevated HR before the jump for novice compared to experienced jumpers.…”
Section: Introductionmentioning
confidence: 98%